Sustainable rice production in African inland valleys: Seizing regional potentials through local approaches - Rodenburg, J.; Zwart, Sander J.; Kiepe, P.; Narteh, L.T.; Dogbe, W.; Wopereis, Marco C.S. (Elsevier, 2014)
With an estimated surface area of 190 M ha, inland valleys are common landscapes in Africa. Due to their general high agricultural production potential, based on relatively high and secure water availability and high soil fertility levels compared to the surrounding uplands, these landscapes could play a pivotal role in attaining the regional objectives of food security and poverty alleviation. Besides agricultural production, i.e. mainly rice-based systems including fish-, vegetable- fruit- and livestock production, inland valleys provide local communities with forest, forage, hunting and fishing resources and they are important as water buffer and biodiversity hot spots. Degradation of natural resources in these vulnerable ecosystems, caused by indiscriminate development for the sole purpose of agricultural production, should be avoided. We estimate that, following improved water and weed management, production derived from less than 10% of the total inland valley area could equal the total current demand for rice in Africa. A significant part of the inland valley area in Africa could hence be safeguarded for other purposes.